Managing data on construction techniques and damage using digital media - Xavier Romão (2013)
Sustainable management and conservation strategies for constructions are known to be highly dependent on the availability of adequate documentation and recordings of relevant data, namely about the structural conditions and the materials of the construction. Available digital technologies have been changing the recording practice by offering new tools to collect, analyse and disseminate information about existing constructions. In this context, the role of GIS-based tools and multimedia technologies in managing and presenting information on existing constructions is addressed herein.